2016
DOI: 10.1177/0265407516665250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of personality on postdivorce partnership trajectories

Abstract: Personality is known to be a key predictor for several aspects of close relationship functioning. Most likely, the influence of this psychological factor is even growing in contemporary societies, where the individual life biography is increasingly the result of personal preferences and less influenced by normative expectations and cultural institutions. In an era of high relationship instability, more and more people engage in a second union. Although it becomes increasingly relevant to study the effects of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Second, singles who choose mobile dating may have particular psychological features that affect the way they form and construct relationships. Certain personality dimensions, such as extraversion or internal locus of control (i.e., the belief that one is in charge of life events and outcomes, as opposed to outside forces), are known to impact mate selection, short-term mating, and marital quality [48][49][50][51][52][53][54]. Individuals that resort to a more agentic way of selecting partners, one that also involves constant interactions with others, may be particularly open, extroverted, and may have a high internal locus of control.…”
Section: Plos Onementioning
confidence: 99%
“…Second, singles who choose mobile dating may have particular psychological features that affect the way they form and construct relationships. Certain personality dimensions, such as extraversion or internal locus of control (i.e., the belief that one is in charge of life events and outcomes, as opposed to outside forces), are known to impact mate selection, short-term mating, and marital quality [48][49][50][51][52][53][54]. Individuals that resort to a more agentic way of selecting partners, one that also involves constant interactions with others, may be particularly open, extroverted, and may have a high internal locus of control.…”
Section: Plos Onementioning
confidence: 99%
“…In our analyses, we examined if the current partner's profile bears a unique similarity to the expartner's (i.e., distinctive similarity), controlling for the extent to which it is normative and is similar to the participant's profile. Additionally, based on literature suggesting that personality influences partnering patterns (20,21), we explored the question of who is more or less likely to be dating a partner similar to their ex-partner by examining the link between participants' Big Five personality traits and each similarity index (i.e., normative, selfpartner, and distinctive similarity indices).…”
Section: The Present Researchmentioning
confidence: 99%
“…The gender constraint of an age penalty did not seem to be more strongly present for women; in fact, it appeared absent for both sexes. One possible explanation is the decreasing likelihood to repartner as divorcees become older (Sodermans et al 2016). The second gender constraint of parenthood also did not show any difference between men and women.…”
Section: Gendermentioning
confidence: 88%
“…What about the personality of the shared partners themselves? Sodermans et al (2016) indicated that neurotic and extraverted individuals would likely not repartner with someone who had more marriage-stabilizing personality traits than their ex-spouse. They found that neurotic divorcees remained mainly single or had multiple relationships.…”
Section: Own Personalitymentioning
confidence: 99%